Singapore - YEO, Tiong Min (Institutional Knowledge at Singapore Management University, 2021)
This chapter discusses the private international law of Singapore in relation to contracts choice of law, with particular reference to and comparison with the Hague Principles on Choice of Law in International Commercial Contracts.